GLUCOCORTICOID INDUCED OSTEOPOROSIS - Peyman Yalçın, (Archives of Rheumatology, 2000)
Glucocorticoids have serious adverse effects on bone metabolism. Long term corticosteroids treatment indu- , ces osteoporosis. The effects of corticosteroids on bone turn över are well known and timingly appropriate preventive approachs may reduce osteoporosis and fractures. İn this revievv glucocorticoids effects on bone metabolism, prophylaxis and treatment are discussed.